MEDB-17. Re-irradiation for recurrent medulloblastoma in a matched cohort: Advantageous especially in patients without resection. (3rd June 2022) - Adolph, Jonas E; Tippelt, Stephan; Tschirner, Sebastian; Gaab, Christine; Mikasch, Ruth; Mynarek, Martin; Rutkowski, Stefan; Warmuth-Metz, Monika; Bison, Brigitte; Pfister, Stefan M; Witt, Olaf; Pietsch, Torsten; et al.
Abstract: INTRODUCTION : Radiotherapy with craniospinal irradiation (CSI) is an important part of initial treatment for medulloblastoma in most children. Radiotherapy after recurrence is currently not widely used. This analysis aims to evaluate whether re-irradiation (RT2) may show survival benefits. METHODS : Data for patients with recurrent medulloblastomas from the German HIT-REZ studies was gathered. Patients with RT2 at 1st recurrence were matched by propensity score to an equal number of patients without radiotherapy. Matching variables were sex, initial therapy, time to recurrence, metastatic stage and therapy at 1st recurrence and radiotherapy at subsequent recurrences. The matched cohort was analysed regarding PFS and OS after 1st recurrence. RESULTS : From a cohort of 240 pre-irradiated patients, 106 patients were matched. Patients with RT2 showed improved median PFS [21.0 months (95%-CI: 17.5 – 27.6)] and OS [37.5 months (CI: 30.0 – 59.4)] compared to control patients [(PFS: 12.0 months (CI: 8.1 – 17.7) / OS: 20.1 months (CI: 14.5 – 44.8)]. When stratifying by resection at recurrence (36.8% resected), a survival advantage for RT2 was found in patients without resection in PFS [19.6 (CI: 14.9 – 31.5) vs. 8.0 months (CI: 5.4 – 14.4)] and OS [41.9 (CI: 30.0 – 59.4) vs. 13.3 months (CI: 8.1 – 36.7)]. However, no advantage was found after resection [PFS: 22.5 (CI: 17.5 – 50.4) vs. 19.1 months (CI: 14.1 – 34.3) / OS: 32.3 (CI: 27.6 – NA) vs. 48 months (CI: 23.4 – NA)]. CSI was used in 6 patients without differences in survival to focal RT2. Median PFS after first irradiation was 32.5 months, after RT2 20.9 months. No patients with RT2 were alive past 10 years after 1st recurrence.CONCLUSION : Patients with recurrent medulloblastoma show benefits from RT2 in median PFS and OS. However, no advantage for RT2 was found when resection was also applied at recurrence. Cure after treatment with RT2 was not found in our cohort.